UMP students use Kad Prihatin Siswa instead of matric cards - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 28 October 2022 - Universiti Malaysia Pahang (UMP) students are now using Kad Prihatin Siswa (RHB Debit-i Card) as a Student Matrix Card after a total of 12,615 students activated their cards gradually since 18 October involving both UMP campuses in Pekan and Gambang.